Actual and ideal sources of coaching knowledge of elite Chinese coaches - He, C.; Trudel, P.; Culver, D. M. (International Journal of Sports Science & Coaching, 2018)
Globalization and advances in technology have created a context where knowledge changes and circulates faster than ever. In high-performance sport coaching, coaches increasingly move from country to country to join national teams - becoming `migrant coaches`. From a coach development perspective, it becomes relevant to investigate how coaches from different countries learn to coach and what would be their ideal sources of knowledge acquisition. Unfortunately, there is a major gap in the English literature regarding Asian coaches. Thus, a study with Chinese gymnastics (Gym) and rhythmic gymnastics (R-Gym) coaches has been conducted. Eighty coaches completed a questionnaire on their actual and ideal sources of knowledge acquisition; 16 of these were interviewed. Data show that the coaches acquired their knowledge (actual) mainly through `being an athlete` and `having a mentor`. Ideally, they would like to have a better balance between these two sources and formal learning situations (courses, seminars, etc.). Another key finding is the barrier resulting from the lack of English knowledge, which is an important limit for Chinese coaches wishing to gather information from abroad, especially through the Internet.